Plague prevention and politics in Manchuria, 1910-1931 (Harvard East Asian monographs., 1967)
Plague prevention in Manchuria became an urgent matter both of public health and of politics in the 1920s and 1930s. If the virulent pneumonic plague could not be quarantined and suppressed, all North China and even nearby countries might be endangered. If China could not deal with the plague, Japan, Russia, and indeed the whole outside world might be justified in moving into Manchuria to do the job, and China's already limited sovereignty there could be further weakened.